Proceedings of the v International Workshop on Modeling, Information Processing and Computing (MIP: Computing-v 2022) 2022
DOI: 10.47813/dnit-mip5/2022-3091-60-65
|View full text |Cite
|
Sign up to set email alerts
|

MLI. Mouse: a new computer vision-based cursor control software

Abstract: The personal computer opens tremendous opportunities for people, whether it is entertainment or work. However, people with disabilities cannot successfully use usual methods of interacting with a computer like a mouse and a keyboard. There are analogs that allow individuals who had disabilities to control the computer using computer vision. They can use their limbs, head, eyes, color markers as reference point, that is used to move a cursor on their computer screen. One of the most popular cursor control softw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
1
0
0
1
Order By: Relevance
“…and earn a living by using computer skills. The results showed in this work are related to previous research, such as [50,51], which found that technological development positively impacts not only daily living activities, which is the objective of the study conducted with EMKEY, but also the brain functions of those who benefit from the technological device created.…”
Section: Yes Yessupporting
confidence: 80%
“…and earn a living by using computer skills. The results showed in this work are related to previous research, such as [50,51], which found that technological development positively impacts not only daily living activities, which is the objective of the study conducted with EMKEY, but also the brain functions of those who benefit from the technological device created.…”
Section: Yes Yessupporting
confidence: 80%
“…в теоретическом, так и прикладном аспекте, прошел в рамках работы четырех секций: кибернетика, вычислительное и имитационное моделирование; прикладная математика и бизнес-информатика; информационные технологии, надежность программного обеспечения и защита данных; обработка информации, программная инженерия и приложения.ОБЗОР ДОКЛАДОВ MIP: COMPUTING-V 2022В данном обзоре представлены работы, которые были включены в программу пленарной сессии. В сборник трудов семинара MIP: Computing-V 2022 включено 16 статей по двум разделам «Кибернетика, вычислительные технологии и имитационное моделирование»[3][4][5][6][7][8][9] и «Информационные технологии, надежность программного обеспечения и защита данных»[10][11][12][13][14][15][16][17][18]. Данные материалы представлены в виде онлайн/видео докладов и презентаций участников (размещены на сайте материалов семинара https://conf.domnit.ru/ru/materialy/mip-computing-5-2022/).Кибернетика, вычислительные технологии и имитационное моделированиеВ работе авторов Д. Мусатова и Д. Петрусевич из МИРЭА -Российского технологического университета на тему «Modeling of forecasts variance reduction at multiple time series prediction averaging with ARMA (1, q) functions»[3] рассматривается комбинация прогнозов временных рядов, что обычно считается хорошим методом на практике.…”
unclassified